Microprocessor theory and applications with 68000/68020 and Pentium - Rafiquzzaman, Mohamed (Hoboken, N.J. : Wiley, 2008)
A self-contained introduction to microprocessor theory and applications. This book presents the fundamental concepts of assembly language programming and system design associated with typical microprocessors, such as the Motorola MC68000/68020 and Intel?
10. ASSEMBLY LANGUAGE PROGRAMMING WITH THE PENTIUM: PART 111. ASSEMBLY LANGUAGE PROGRAMMING WITH THE PENTIUM: PART 2; 12. PENTIUM HARDWARE AND INTERFACING; APPENDIX A: ANSWERS TO SELECTED PROBLEMS; APPENDIX B: GLOSSARY; APPENDIX C: MOTOROLA 68000 AND SUPPORT CHIPS; APPENDIX D: 68000 EXECUTION TIMES; APPENDIX E: 68000 / SELECTED 68020 INSTRUCTION SET; APPENDIX F: PENTIUM INSTRUCTION FORMAT AND TIMING; APPENDIX G: PENTIUM INSTRUCTION SE.
Includes bibliographical references (pages 563-564) and index.
Print version record.
John Wiley and Sons
Keywords: Motorola 68000 series microprocessors; Pentium (Microprocessor); Motorola 68000 (Famille de microprocesseurs); Pentium (Microprocesseur); COMPUTERS -- Hardware -- Personal Computers -- Macintosh; COMPUTERS -- Hardware -- Personal Computers -- PCs; Motorola 68000 series microprocessors; Pentium (Microprocessor)